UPAYA HUKUM PERLINDUNGAN RAHASIA DAGANG WARALABA (FRANCHISE) PADA BIMBINGAN BELAJAR - I Gede Putu Mantra; Desyanti Suka Asih K. Tus; Ni Luh Mia Lastinia (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
One of the Intellectual Property Rights that plays animportant role in the franchise business is Trade Secrets. Global business competition makes it necessary to provide protection for Trade Secrets in order to create a healthy business world. Franchise business systems can be carried out in various fields, namely the field of goods and services. One of them is tutoring, namely the Franchise business in the service sector. One of the agreements in the tutoring franchise agreement is about trade secrets. Franchise cooperation agreement in tutoring is to provide a license for the utilization or use of Trade Secrets for a certain period of time. The owner of a Trade Secret allows his business partner to use some of his Trade Secret to run a business, so this can open an opportunity or loophole to violate the confidentiality of the Trade Secret.Legal remedies against violations of Trade Secrets in tutoring can be made based on the provisions of Article 12 of Law no. 30 of 2000 concerning Trade Secrets. Settlement of cases related to Trade Secrets can not only be done through arbitration and through the ADR (Alternative Dispute Resolution) route, besides that it can be carried out based on criminal law, as well as based on civil law. Cases of violation of Trade Secrets in tutoring may be subject to sanctions based on Article 17 Paragraph (1) of the Trade Secrets Law. Violation of Trade Secrets also includes unlawful acts based on Article 1365 of the Civil Code. Meanwhile, violations of Trade Secrets in criminal law are included in opening secrets, which are contained in Article 322 Paragraph (1) of the Criminal Code.